2019
DOI: 10.1016/j.joule.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Chemicals and Materials from Bacterial Aromatic Catabolic Pathways

Abstract: Intermediates of bacterial aromatic catabolism contain chemical functionality that could enable them to serve as precursors to environmentally compatible materials with similar or superior properties relative to petroleum-derived incumbents. Here, Pseudomonas putida was engineered to convert aromatic molecules and glucose into 16 of these metabolic intermediates including muconic acid, which was produced at a 41% yield from glucose. Several of these molecules were then polymerized to generate performance-advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
159
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(161 citation statements)
references
References 54 publications
1
159
1
Order By: Relevance
“…[ 146 ] Aromatic compounds derived from lignin could offer chemical functionality as intermediates of bacterial aromatic degradation pathway. [ 147 ] Similarly, using TPA, which is aromatic compound formed from depolymerization of PET wastes, as a substrate would probably be advantageous for the production of various value‐added compounds via aromatic catabolism based on catechol or protocatechuic acid. Recently, recombinant E. coli harboring TPA degradation pathway could biologically convert TPA, derived from hydrolysis of waste PET, into value‐added biochemicals such as 2‐pyrone‐4,6‐dicarboxylic acid, vanillic acid, gallic acid, pyrogallol, catechol, and muconic acid by using single or concerted reactions such as hydroxylation, decarboxylation, oxidative ring cleavage, and/or methylation.…”
Section: Resource Circularity Of Biopolymers In Plastic Waste Refineriesmentioning
confidence: 99%
“…[ 146 ] Aromatic compounds derived from lignin could offer chemical functionality as intermediates of bacterial aromatic degradation pathway. [ 147 ] Similarly, using TPA, which is aromatic compound formed from depolymerization of PET wastes, as a substrate would probably be advantageous for the production of various value‐added compounds via aromatic catabolism based on catechol or protocatechuic acid. Recently, recombinant E. coli harboring TPA degradation pathway could biologically convert TPA, derived from hydrolysis of waste PET, into value‐added biochemicals such as 2‐pyrone‐4,6‐dicarboxylic acid, vanillic acid, gallic acid, pyrogallol, catechol, and muconic acid by using single or concerted reactions such as hydroxylation, decarboxylation, oxidative ring cleavage, and/or methylation.…”
Section: Resource Circularity Of Biopolymers In Plastic Waste Refineriesmentioning
confidence: 99%
“…ISTKB was shown to use 4-HBA for growth and production of polyhydroxyalkanoate biopolyesters [20]. Other examples include the biological funneling of 4-HBA into valuable catabolic pathway intermediates such as muconic acid, 2-pyrone-4,6-dicarboxylic acid, beta-ketoadipic acid, and isocinchomeronic acid using engineered strains of Novosphingobium aromaticivorans and Pseudomonas putida [21][22][23].…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…Indeed, a recent techno-economic analysis (TEA) accounting for both fixed and variable costs concluded that a fully biological route to adipic acid from glucose would result in an adipic acid price point of $1.36/kg, while fully chemical and hybrid biological and chemical routes would result in price points of $1.56/kg and $1.48/kg 10 . A separate TEA showed that switching feedstock from glucose to lignin monomers reduced adipic acid minimum selling price by 50% due to increased productivity and decreased feedstock cost 12 . Taken together, lignin is a more desirable feedstock than sugars for adipic acid production.…”
Section: Introductionmentioning
confidence: 99%
“…showed that switching feedstock from glucose to lignin monomers reduced adipic acid minimum selling price by 50% due to increased productivity and decreased feedstock cost 12 . Taken together, lignin is a more desirable feedstock than sugars for adipic acid production.…”
mentioning
confidence: 99%